'Boost Camp', a universal school-based transdiagnostic prevention program targeting adolescent emotion regulation; evaluating the effectiveness by a clustered RCT: a protocol paper - Brenda Volkaert; Laura Wante; Leentje Vervoort; Caroline Braet (BMC, 2018)
Abstract Background The transition from childhood into adolescence can be considered as a critical developmental period. Moreover, adolescence is associated with a decreased use of adaptive emotion regulation strategies and an increased use of maladaptive emotion regulation strategies increasing the risk of emotional problems. Targeting emotion regulation is therefore seen as an innovative prevention approach. The present study aims to evaluate the effectiveness of Boost camp, an innovative school-based prevention program targeting ER, on adolescents' emotion regulation skills and emotional wellbeing. Also secondary outcomes and possible moderators will be included. Methods The aim is to reach 300 adolescents (16 class groups, 6 schools) in their first year of high school. A clustered Randomized Controlled Trial (RCT) with two conditions, intervention (n = 150) and control (n = 150), will be set up. Adolescents in the intervention condition will receive 14 lessons over the course of 2 days, followed by Booster sessions, and will be compared with adolescents in a non-intervention control group. The outcomes will be measured by self-report questionnaires at baseline, immediately after Boost camp, and at three and 6 months follow-up. Discussion Data-collection is planned to be completed in May 2018. Data-analyses will be finished the end of 2018. The presented paper describes the Boost camp program and the clustered RCT design to evaluate its effectiveness. It is expected that Boost camp will have beneficial effects. If found effective, Boost camp will have the potential to increase adolescent's ER and well-being, and reduce the risk to become adults in need. The trials is registered on the 13th of June 2017 in ISRCTN registry [ISRCTN68235634].